2002
DOI: 10.1042/cs20010357
|View full text |Cite
|
Sign up to set email alerts
|

Finapres arterial pulse wave analysis with Modelflow is not a reliable non-invasive method for assessment of cardiac output

Abstract: A B S T R A C TNon-invasive continuous monitoring of cardiac output could be very useful in clinical care and in research settings, particularly in elderly subjects. We studied whether Finapres arterial pulse wave analysis with Modelflow2 is a reliable non-invasive method for the assessment of cardiac output in healthy elderly subjects. We compared Modelflow2 cardiac output (MFCO) with thermodilution cardiac output (TDCO) in 28 healthy subjects, aged 70p4 years (meanpS.D.). TDCO was measured during right-sided… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
2
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 24 publications
(36 reference statements)
1
29
2
1
Order By: Relevance
“…In a study using a different pulse contour analysis method, it was shown that this method is not suitable for measuring absolute cardiac output values during exercise in healthy individuals (33). However, it was also demonstrated that initial calibration with another method improved the accuracy substantially (38).…”
Section: Discussionmentioning
confidence: 99%
“…In a study using a different pulse contour analysis method, it was shown that this method is not suitable for measuring absolute cardiac output values during exercise in healthy individuals (33). However, it was also demonstrated that initial calibration with another method improved the accuracy substantially (38).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have validated the ModelFlow method compared with the standard invasive techniques (thermodilution and pulse dye densitometry) and indicate that this method provides a reliable estimate of changes in cardiac output in healthy exercising humans (Matsukawa et al 2004), patients with septic shock (Jellema et al 1999) or during prolonged tilt testing (Harms et al 1999). However, the validity of absolute ModelFlow estimates are uncertain during initial changes in posture or with ageing (Remmen et al 2002). Therefore, the emphases of these data are on comparative changes because ModelFlow-derived estimates of SV and Á Q track group-averaged changes reliably (Leonetti et al 2004).…”
Section: Limitationsmentioning
confidence: 99%
“…Our study is in line with their observation. The method of pulse wave analysis for assessment of stroke volume, without invasive calibration may be imprecise (21), however, in emergency medicine the distinctive capacity of a parameter is important, rather than its precisity, compared to a "gold standard". The scarce availability of stroke volume analysis is a limitation yet.…”
Section: Discussionmentioning
confidence: 99%